1996
DOI: 10.1002/(sici)1097-4695(199605)30:1<67::aid-neu7>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and cell death in olfactory epithelium

Abstract: The olfactory epithelium (OE) of the mammal is uniquely suited as a model system for studying how neurogenesis and cell death interact to regulate neuron number during development and regeneration. To identify factors regulating neurogenesis and neuronal death in the OE, and to determine the mechanisms by which these factors act, investigators studied OE using two major experimental paradigms: tissue culture of OE; and ablation of the olfactory bulb or severing the olfactory nerve in adult animals, procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…TUNEL-positive cells decreased in number and reached the control level 5 days after bulbectomy (Holcomb et al, 1995). the same time a peak loss of ORNs as measured by epithelial thickness was observed in the septal OE (Calof et al, 1996). Using scanning electron microscopy, almost a total absence of ORNs in the hamster OE was found 4 days after bulbectomy (Morrison & Costanzo, 1989).…”
Section: Apoptosis After Bulbectomymentioning
confidence: 75%
“…TUNEL-positive cells decreased in number and reached the control level 5 days after bulbectomy (Holcomb et al, 1995). the same time a peak loss of ORNs as measured by epithelial thickness was observed in the septal OE (Calof et al, 1996). Using scanning electron microscopy, almost a total absence of ORNs in the hamster OE was found 4 days after bulbectomy (Morrison & Costanzo, 1989).…”
Section: Apoptosis After Bulbectomymentioning
confidence: 75%
“…The idea that cell death may be necessary to induce new cell production is supported by studies that have found increased neurogenesis after targeted apoptosis (Calof et al, 1996). A number of specific local molecular cues or cell-autonomous factors are candidates for mediating injury-induced increases in proliferating basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, lagomorphs and non-human primates, olfaction is still one of the predominant senses. The fact that the neural epithelium in the nasal mucosa consists of a local pool of constantly regenerating neurons [31] may provide a clue as to why neurogenesis occurs in brain structures that are part of the olfactory system. The axons from the continually regenerating olfactory receptor cells project to the olfactory bulb, where a robust pool of newly generated neurons occurs that is derived from the SVZ via the RMS [5].…”
Section: Discussionmentioning
confidence: 99%